Acantholytic oral squamous cell carcinoma with clear cell change - a rare amalgamated variant - Gitika Sharma; Anju Devi; Mala Kamboj; Anjali Narwal (University of São Paulo, 2023)
Background: Acantholytic squamous cell carcinoma (ASCC) is an uncommon histological variation of oral squamous cell carcinoma (OSCC), accounting for fewer than 4% of all occurrences. The tumor shows a slight masculine predisposition, with the lower lip being the most commonly affected location. ASCC is reported to have a diverse biologic behavior, which explains its ability to metastasize to distant places and, thus, its poor prognosis. Similarly, clear cell change in OSCC is a rare occurrence with an unknown etiology that suggests its aggressive nature. Method and Results: Histopathology reveals central acantholytic cells with numerous duct-like features. The presence of distinct cytological atypia contributes to the diagnosis of SCC. Special stains and IHC aid in distinguishing tumor from other histopathologically similar entities. Conclusion: The case of a 29-year-old male presented here with an updated literature review highlights the need for histological study of the unique and seldom seen oral ASCC with clear cell change, which can be ignored because of similarities with other entities. Because recurrence rates are so high for ASCC, amalgamated clear cell change makes it critical for proper treatment initiation with a definite diagnosis. To the best of our knowledge, this is the first documented occurrence. Our experience with the present case suspected a more aggressive behavior due to a high Ki-67 index, anticipating a poorer prognosis in the oral cavity considering the patient's young age.